Three-silver Low-E coated glass and preparation method thereof
By using Ni-doped ZnSe as a combination of reinforcement layer and multi-layer structure in Sanyin Low-E coated glass, the problems of insufficient oxidation resistance and poor wear resistance of existing Low-E coated glass are solved, and better thermal insulation performance and mechanical strength are achieved.
Patent Information
- Application Number
- CN202411814795.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
The existing double-silver or triple-silver Low-E coating glass has problems of insufficient oxidation resistance and poor wear resistance, which affects its thermal insulation performance and service life.
Using Ni-doped ZnSe as the reinforcement layer, multi-layer structures such as Ni-doped ZnSe, silver layer, aluminum-doped zinc oxide layer and NiCr layer were deposited on the glass substrate by magnetron sputtering to form a tri-silver Low-E coated glass, and a polyethyleneimine composite and DLC coating were provided between the film layers to improve thermal insulation performance and mechanical strength.
It significantly improves the weather resistance and thermal insulation performance of Sanyin Low-E coated glass, improves the hardness and mechanical processing performance of the film layer, extends the storage cycle of the product and reduces quality problems in transportation and processing.
Smart Images

Figure BDA0005181466600000081 
Figure BDA0005181466600000082
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coated glass, and in particular relates to triple-silver Low-E coated glass and a preparation method thereof. Background Art
[0002] Glass is an important building material. Most modern high-rise buildings use glass curtain walls. Currently, people generally use single-layer flat glass on glass curtain walls. It has good light transmittance, but poor heat insulation effect. Infrared rays outside the window can easily radiate into the room through the glass, causing high indoor temperatures, especially in summer. Excessively high indoor temperatures can easily cause human discomfort and waste electricity for air conditioning. Low-emissivity coated glass is thus produced.
[0003] Low-E coated glass is also called Low-E glass. During the manufacturing process, one or more layers of metal materials need to be deposited on the surface of the float glass to reflect the near-infrared rays in the sunlight and the far-infrared rays in the living environment, thereby reducing the glass's absorption rate and radiation rate of infrared rays. In summer, it can effectively prevent the near-infrared rays in the sunlight from entering the room, avoid the indoor temperature from rising, and save air conditioning costs; in winter, it can prevent the far-infrared rays generated by indoor heating from escaping to the outside, maintain the indoor temperature, save heating costs, and bring economic compensation to users. However, the double-silver or triple-silver Low-E coated glass currently produced generally has problems such as insufficient antioxidant performance and poor wear resistance. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a triple-silver Low-E coated glass and a preparation method thereof, which can effectively improve the weather resistance and heat insulation performance of the glass.
[0005] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0006] The object of the present invention is to provide a triple-silver Low-E coated glass, comprising a glass substrate, and a strengthening layer, a first functional layer, a second functional layer, a third functional layer and a protective layer stacked in sequence from bottom to top on at least one surface of the glass substrate; a first barrier layer is arranged between the first functional layer, the second functional layer and the third functional layer; and a second barrier layer is arranged between the third functional layer and the protective layer.
[0007] Furthermore, the reinforcement layer is a Ni-doped ZnSe layer, and its thickness is 5-10 nm.
[0008] The Ni-doped ZnSe of the present invention is used as a strengthening layer. ZnSe has excellent high temperature resistance and can prevent Na ions in the glass substrate from diffusing into the film system to damage the Ag layer during high temperature tempering or bending. This can make the entire film system of the triple-silver low-emissivity glass have better heat resistance under high temperature conditions. In addition, after Ni is doped, the strength of the film layer is further improved, thereby increasing the hardness of the film layer of the triple-silver Low-E coated glass and making it have better mechanical processing performance.
[0009] Furthermore, the preparation method of Ni-doped ZnSe is:
[0010] In an argon atmosphere with a pressure of 1.0 to 6.0×10-3 mbar, Ni is doped into a ZnSe target by a magnetron sputtering method.
[0011] Furthermore, the first functional layer, the second functional layer and the third functional layer are silver layers, and the thicknesses thereof are all 10-15 nm.
[0012] Furthermore, the first barrier layer includes a NiCr layer and an aluminum-doped zinc oxide layer stacked in sequence from top to bottom, and the thickness of the NiCr layer and the thickness of the aluminum-doped zinc oxide layer are both less than 10 nm.
[0013] Furthermore, the ratio of the thickness of the NiCr layer to the thickness of the aluminum-doped zinc oxide layer is 0.3 to 0.5.
[0014] Furthermore, the thickness of the NiCr layer is 2.4 nm, and the thickness of the aluminum-doped zinc oxide layer is 8 nm.
[0015] Furthermore, the thickness of the NiCr layer is 5 nm, and the thickness of the aluminum-doped zinc oxide layer is 10 nm.
[0016] The present invention forms a first barrier layer by combining an aluminum-doped zinc oxide layer (AZO) and a NiCr layer. AZO is a material with high thermal stability and low infrared radiation rate, which can prevent outdoor high temperature from being transmitted to the indoor through radiation, and has a good heat insulation effect. NiCr is a high-strength and corrosion-resistant alloy material with good chemical stability and thermal properties, which can protect the Ag layer from being damaged and prevent the Ag layer from being oxidized, thereby improving the mechanical strength and corrosion resistance of the glass. In addition, the inventors have found through research in the actual preparation process that there are strict requirements for the setting order and thickness of the two. By coating in a specific order and then within a specific thickness range, the transmittance and heat insulation can show optimal characteristics.
[0017] Furthermore, the second barrier layer is a polyethyleneimine composite film layer having a thickness of 5 to 10 nm, and the preparation method is as follows:
[0018] A copper sulfate solution with a concentration of 0.01 to 0.5 mg / mL is added to a polyethyleneimine solution with a concentration of 0.5 to 1.5 mg / mL, and after ultrasonic dispersion for 20 to 30 minutes, continuous stirring is performed for 20 to 24 hours, and reduced pressure concentration is performed to obtain a composite for preparing a second barrier layer.
[0019] Furthermore, the volume ratio of the copper sulfate solution to the polyethyleneimine solution is 0.5-1.
[0020] The present invention uses a polyethyleneimine composite as the second barrier layer. The polyethyleneimine has excellent air tightness, good heat insulation performance, and high reflectivity to light, which greatly reduces the absorption and transfer of heat. When copper ions are doped in it, the copper ions will chelate with the amine groups in the polyethyleneimine, further improving its heat insulation performance and light reflectivity.
[0021] Furthermore, the protective layer is a DLC coating with a thickness of 10 to 15 nm.
[0022] Another object of the present invention is to provide a method for preparing the triple-silver Low-E coated glass, which comprises:
[0023] A reinforcing layer, a first functional layer, a first barrier layer, a second functional layer, a first barrier layer, and a third functional layer are sequentially deposited on a glass substrate by magnetron sputtering, and then a second barrier layer is coated between the third functional layer and the protective layer, and then the protective layer is continuously deposited.
[0024] Beneficial effects of the present invention:
[0025] The present invention can effectively prevent triple-silver Low-E coated glass from being scratched by glass scraps and small particles during cutting, edge grinding, heat treatment, transportation, etc., and significantly improves its wear resistance. At the same time, it also exhibits excellent light transmittance and heat insulation. DETAILED DESCRIPTION
[0026] The specific implementation modes of the present invention are described below to facilitate those skilled in the art to understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0027] Embodiment 1:
[0028] A triple-silver Low-E coated glass, the preparation method of which is as follows:
[0029] (1) Soak the float glass substrate in a potassium permanganate concentrated sulfuric acid solution for 18 hours, then rinse with deionized water, then ultrasonically clean it in acetone and ethanol for 10 minutes, then rinse it with deionized water for 5 minutes, dry it with nitrogen, and set it aside;
[0030] (2) Depositing a strengthening layer with a thickness of 10 nm on float glass by magnetron sputtering in an argon atmosphere with a pressure of 2.4×10-3 mbar, with the target material being ZnSe / Ni;
[0031] (3) depositing a first functional layer with a thickness of 11.6 nm by magnetron sputtering in an argon atmosphere at a pressure of 3.0×10-3 mbar, using Ag as the target material;
[0032] (4) in an argon atmosphere at a pressure of 3.4×10-3 mbar, depositing AZO with a thickness of 10 nm by magnetron sputtering, and then depositing NiCr with a thickness of 5 nm to form a first barrier layer;
[0033] (5) depositing a second functional layer with a thickness of 11.6 nm in the same manner as step (3);
[0034] (6) depositing a first barrier layer between the second functional layer and the third functional layer in the manner of step (4);
[0035] (7) depositing a third functional layer with a thickness of 11.6 nm in the same manner as step (3);
[0036] (8) A second barrier layer with a thickness of 5 nm is coated on the third functional layer. The second barrier layer is made of a polyethyleneimine composite and is prepared as follows:
[0037] A 0.5 mg / mL copper sulfate solution was added to a 1.5 mg / mL polyethyleneimine solution, with a volume ratio of 0.5; after ultrasonic dispersion for 30 minutes, the mixture was continuously stirred for 24 hours, and concentrated under reduced pressure to obtain a polyethyleneimine complex for preparing a second barrier layer;
[0038] (9) In an argon atmosphere with a gas pressure of 3.2×10-3 mbar, a protective layer with a thickness of 12 nm was deposited by magnetron sputtering, with the target material being DLC, to obtain the triple-silver Low-E coated glass.
[0039] Embodiment 2:
[0040] A triple-silver Low-E coated glass, the preparation method of which is as follows:
[0041] (1) Soak the float glass substrate in a potassium permanganate concentrated sulfuric acid solution for 18 hours, then rinse with deionized water, then ultrasonically clean it in acetone and ethanol for 10 minutes, then rinse it with deionized water for 5 minutes, dry it with nitrogen, and set it aside;
[0042] (2) In an argon atmosphere at a pressure of 3.4×10-3 mbar, a strengthening layer with a thickness of 8.4 nm was deposited on float glass by magnetron sputtering, with the target material being ZnSe / Ni;
[0043] (3) depositing a first functional layer with a thickness of 10 nm by magnetron sputtering in an argon atmosphere at a pressure of 3.2×10-3 mbar, with the target material being Ag;
[0044] (4) in an argon atmosphere at a pressure of 3.2×10-3 mbar, depositing AZO with a thickness of 5 nm by magnetron sputtering, and then continuing to deposit NiCr with a thickness of 1.5 nm to form a first barrier layer;
[0045] (5) depositing a second functional layer with a thickness of 10 nm in the same manner as step (3);
[0046] (6) depositing a first barrier layer between the second functional layer and the third functional layer in the manner of step (4);
[0047] (7) depositing a third functional layer with a thickness of 10 nm in the same manner as in step (3);
[0048] (8) A second barrier layer with a thickness of 10 nm is coated on the third functional layer. The second barrier layer is made of a polyethyleneimine composite and is prepared as follows:
[0049] A 0.5 mg / mL copper sulfate solution was added to a 1.5 mg / mL polyethyleneimine solution, with the volume ratio of the two being 1; after ultrasonic dispersion for 20 minutes, the mixture was continuously stirred for 20 hours, and concentrated under reduced pressure to obtain a polyethyleneimine complex for preparing a second barrier layer;
[0050] (9) In an argon atmosphere at a pressure of 2.6×10-3 mbar, a protective layer with a thickness of 15 nm was deposited by magnetron sputtering, with the target material being DLC, to obtain the triple-silver Low-E coated glass.
[0051] Embodiment 3:
[0052] A triple-silver Low-E coated glass, the preparation method of which is as follows:
[0053] (1) Soak the float glass substrate in a potassium permanganate concentrated sulfuric acid solution for 18 hours, then rinse with deionized water, then ultrasonically clean it in acetone and ethanol for 10 minutes, then rinse it with deionized water for 5 minutes, dry it with nitrogen, and set it aside;
[0054] (2) Depositing a strengthening layer with a thickness of 5 nm on float glass by magnetron sputtering in an argon atmosphere with a pressure of 4.2×10-3 mbar, with the target material being ZnSe / Ni;
[0055] (3) depositing a first functional layer with a thickness of 15 nm by magnetron sputtering in an argon atmosphere at a pressure of 3.4×10-3 mbar, with the target material being Ag;
[0056] (4) in an argon atmosphere at a pressure of 3.2×10-3 mbar, depositing AZO with a thickness of 8 nm by magnetron sputtering, and then continuing to deposit NiCr with a thickness of 3.2 nm to form a first barrier layer;
[0057] (5) depositing a second functional layer with a thickness of 15 nm in the same manner as step (3);
[0058] (6) depositing a first barrier layer between the second functional layer and the third functional layer in the manner of step (4);
[0059] (7) depositing a third functional layer with a thickness of 15 nm in the same manner as in step (3);
[0060] (8) A second barrier layer with a thickness of 8 nm is coated on the third functional layer. The second barrier layer is made of a polyethyleneimine composite and is prepared as follows:
[0061] A 0.5 mg / mL copper sulfate solution was added to a 0.5 mg / mL polyethyleneimine solution, with a volume ratio of 0.5; after ultrasonic dispersion for 30 minutes, the mixture was continuously stirred for 24 hours, and concentrated under reduced pressure to obtain a polyethyleneimine complex for preparing a second barrier layer;
[0062] (9) In an argon atmosphere at a pressure of 3.6×10-3 mbar, a protective layer with a thickness of 10 nm was deposited by magnetron sputtering, with the target material being DLC, to obtain the triple-silver Low-E coated glass.
[0063] Comparative Example 1:
[0064] Compared with Example 1, no reinforcement layer is included, and the rest of the process is consistent with Example 1.
[0065] Comparative Example 2:
[0066] Compared with Example 1, the target material of the strengthening layer is ZnSe, and does not contain the second barrier layer. The rest of the process is consistent with Example 1.
[0067] Comparative Example 3:
[0068] Compared with Example 1, the first barrier layer only contains AZO, the second barrier layer only uses polyethyleneimine, and the rest of the process remains the same as Example 1.
[0069] Comparative Example 4:
[0070] Compared with Example 1, the deposition order of AZO and NiCr in the first barrier layer is opposite, and the rest of the process is consistent with Example 1.
[0071] Comparative Example 5:
[0072] Compared with Example 1, the deposition order of AZO and NiCr in the first barrier layer is opposite, the thickness of AZO is 10 nm, and the thickness of NiCr is 1 nm. The rest of the process is consistent with Example 1.
[0073] Comparative Example 6:
[0074] Compared with Example 1, the thickness of AZO in the first barrier layer is 15 nm, the thickness of NiCr is 2 nm, and the rest of the process is consistent with Example 1.
[0075] Comparative Example 7:
[0076] Compared with Example 1, the thickness of AZO in the first barrier layer is 2 nm, the thickness of NiCr is 10 nm, and the rest of the process is consistent with Example 1.
[0077] The triple-silver Low-E coated glass obtained in Examples 1 to 3 and Comparative Examples 1 to 3 was subjected to a heat treatment at 500° C., including bending, tempering and other processes, and then the hardness grade change before and after the heat treatment was detected by a pencil hardness test. The results are shown in Table 1.
[0078] Table 1 Heat resistance and mechanical properties of triple silver Low-E coated glass
[0079]
[0080] The performance of the triple-silver Low-E coated glass prepared in Examples 1 to 3 and Comparative Examples 3 to 7 was tested in accordance with GB / T2680-94 "Determination of visible light transmittance, direct sunlight transmittance, total solar energy transmittance, ultraviolet light transmission ratio and related window glass parameters for architectural glass" and JGJ / T151-2008. The results are shown in Table 2.
[0081] Table 2 Triple silver Low-E coated glass performance
[0082]
[0083] According to the test results in Table 1 and Table 2, the heat resistance, light transmittance, and thermal insulation performance of the triple-silver Low-E coated glass prepared by the technical solution of the present invention are significantly better than those of Comparative Examples 1 to 7. In addition, in product transportation, storage, and processing experiments, it is found that its storage cycle is significantly increased, and the quality problems caused by storage and handling are greatly improved.
[0084] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A triple silver Low-E coated glass, characterized in that: The invention comprises a glass substrate, and a strengthening layer, a first functional layer, a second functional layer, a third functional layer and a protective layer stacked in sequence from bottom to top on at least one surface of the glass substrate; a first barrier layer is arranged between the first functional layer, the second functional layer and the third functional layer; and a second barrier layer is arranged between the third functional layer and the protective layer.
2. The triple silver Low-E coated glass according to claim 1, characterized in that: The strengthening layer is a Ni-doped ZnSe layer, and its thickness is 5-10 nm.
3. The triple-silver Low-E coated glass according to claim 2, characterized in that: The preparation method of Ni-doped ZnSe is: In an argon atmosphere, Ni was doped into the ZnSe target by magnetron sputtering.
4. The triple silver Low-E coated glass according to claim 1, characterized in that: The first functional layer, the second functional layer and the third functional layer are silver layers, and the thicknesses thereof are all 10-15 nm.
5. The triple silver Low-E coated glass according to claim 1, characterized in that: The first barrier layer includes a NiCr layer and an aluminum-doped zinc oxide layer stacked in sequence from top to bottom, and the thickness of the NiCr layer and the thickness of the aluminum-doped zinc oxide layer are both less than 10 nm.
6. The triple-silver Low-E coated glass according to claim 5, characterized in that: The ratio of the thickness of the NiCr layer to the thickness of the aluminum-doped zinc oxide layer is 0.3-0.
5.
7. The triple silver Low-E coated glass according to claim 1, characterized in that: The second barrier layer is a polyethyleneimine composite film layer having a thickness of 5 to 10 nm, and the preparation method is as follows: A copper sulfate solution with a concentration of 0.01 to 0.5 mg / mL is added to a polyethyleneimine solution with a concentration of 0.5 to 1.5 mg / mL, and after ultrasonic dispersion for 20 to 30 minutes, continuous stirring is performed for 20 to 24 hours, and reduced pressure concentration is performed to obtain a composite for preparing a second barrier layer.
8. The triple-silver Low-E coated glass according to claim 7, characterized in that: The volume ratio of the copper sulfate solution to the polyethyleneimine solution is 0.5-1.
9. The triple-silver Low-E coated glass according to claim 1, characterized in that: The protective layer is a DLC layer, and the thickness of the DLC layer is 10-15 nm.
10. A method for preparing triple-silver Low-E coated glass according to any one of claims 1 to 9, characterized in that: include: A reinforcing layer, a first functional layer, a first barrier layer, a second functional layer, a first barrier layer, and a third functional layer are sequentially deposited on a glass substrate by magnetron sputtering, and then a second barrier layer is coated between the third functional layer and the protective layer, and then the protective layer is continuously deposited.